THE EFFECT OF PAYLATER USE ON IMPULSE SHOPPING BEHAVIOR AMONG STUDENTS: A REVIEW FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Amna Lathiva Putri H; Diyah Ayu Safitri; Faadlilla; Indri Sulistiani; Mufidtri Mazakiyya; Riska Ramadhani; Tarisma Triana; Tiara Indah Sasmita (Journal Informatic, Education and Management (JIEM), 2026)
The development of financial technology (fintech) has encouraged the emergence of the PayLater service as an alternative payment method in e-commerce transactions. The ease of access and flexibility offered make PayLater increasingly in demand, including among students. However, the use of PayLater also raises concerns because it can encourage impulsive shopping behavior that has the potential to have an impact on users' financial condition. This study aims to analyze the influence of PayLater use on impulse shopping behavior and review the phenomenon from the perspective of Islamic economics. The research uses a descriptive qualitative approach with a literature review method through the review of various scientific journals, books, and relevant reference sources regarding PayLater, impulse shopping behavior, financial literacy, and Islamic economics. The results of the study show that the ease of access to PayLater services, intensive promotional strategies, and low financial literacy contribute to the increasing tendency of impulsive shopping behavior. Uncontrolled use of PayLater can lead to excessive consumption, financial stress, and increased debt risk. From an Islamic economic perspective, consumption behavior should be carried out wisely by avoiding israf (excess), tabdzir (waste), and the element of usury in transactions. Therefore, improving financial literacy and self-control is needed to encourage a more responsible use of PayLater, especially among students.